SOCIO-ECONOMIC IMPACT OF THE RELOCATION POLICY OF MOUNT SINABUNG VICTIMS: COMPARISON OF FIRST AND SECOND STAGES - Nina Novira; Tumiar Sidauruk; Elfayetti Elfayetti; Herdi Herdi; Nur Saidah Siregar (GeoEco, 2025)
The series of eruptions from Mount Sinabung in recent years caused significant damage to the surrounding villages. This led to the implementation of a relocation policy. Three villages were relocated to the Siosar Relocation Area in the first stage, while four other villages were given the freedom to choose their new homes in the second relocation stage. The villagers moved from their hometowns to new places to start fresh lives. This raised questions about the relationships and social status of the relocated communities. The villagers lost their agricultural land. The government provided 0.5 hectares of land for farming for those who were moved to the Siosar Relocation Area and cash amounting to Rp. 20,000,000 for the second stage. However, the new land had different edaphic conditions, steeper topography, cooler temperatures, and new marketing arrangements. This raised questions about how these new conditions affected the economy of the relocated communities in both the first and second stages. Using a qualitative approach, this study applied in-depth interviews and direct observations. The findings showed differences in the social and economic conditions of the relocated communities between the two stages. Overall, the economic and social conditions of the people moved to the siosar relocation area were better compared to those who received cash in the relocation stage.